The science behind One Health: at the interface of humans, animals, and the environment. Issue 1 (May 2017) - Murtaugh, Michael P.; Steer, Clifford J.; Sreevatsan, Srinand; Patterson, Ned; Kennedy, Shaun; Sriramarao, P.
Abstract : Humans face a grand quality‐of‐life challenge as growing demands for resources for an ever‐expanding population threaten the existence of wildlife populations, degrade land, and pollute air and water. Public investment and policy decisions that will shape future interactions of humans, animals, and the environment need scientific input to help find common ground for durable and sustainable success. The Second International Conference on One Medicine One Science brought together a broad range of scientists, trainees, regulatory authorities, and health experts from 34 countries to inform and discuss the human impacts of air quality; the complexities of water quality, access, and conflicts; the opportunities and uncertainties in precision medicine; and the role of science communication in health policy formulation. Workshops focused on the roles and development of physician–scientists and multidisciplinary teams in complex problem solving, Big Data tools for analysis and visualization, international policy development processes, and health models that benefit animals and humans. Key realizations were that local and regional health challenges at the interface of humans, animals, and the environment are variations of the same overarching conflicts and that international gatherings provide new opportunities for investigation and policy development that are broadly applicable.